Calixarene based nanocomposite materials for high performance supercapacitor electrode - Waghmode, Babasaheb J.; Soni, Roby; Patil, Kashinath Rangu; Malkhede, Dipalee D. (New Journal of Chemistry, 2017)
A functionalised calixarene {4-Sulphatocalix [6] arene Hydrate (SC6)} stabilises MoS2/partially reduced graphene oxide (rGO) nanosheet. Such stabilised SC6-rGO/SC6-MoS2 and SC6 doped polyaniline (PANI) together forms a nanocomposite hybrid material for supercapacitor electrode. It was fabricated by an in situ polymerization method. Transmission electron microscopy (TEM) results suggest that PANI nanostructures grow homogeneously onto the surfaces of SC6 functionalised MoS2. Calixarene acts as a dopant for PANI as well as a stabiliser for the 2D nanosheets of rGO/MoS2. The characterisation of composites together with basic components was done by using various techniques namely, solid-state FT-IRspectroscopy, X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD). The electrochemical performance was analysed by cyclic voltammetry (CV), galvanostatic charge/discharge and electrochemical impedance spectrometry (EIS). It was found that the SC6 functionalised MoS2 and SC6 doped PANI formed a uniform nanocomposite. The synthesised composites show high specific capacitance (691 F/g) and good cycling stability during the charge-discharge process when used as supercapacitor electrodes. The improvement in electrochemical performance of composites is assigned to synergistic effect of SC6 stabilised MoS2 and doped PANI. Our investigation highlighted the importance of use of calixarene in composites for above stated supercapacitor performance. The role of calixarene in the present study opens a way for the application of alike materials in the composite supercapacitors for energy storage applications.